Remoção de íons metálicos de soluções aquosas utilizando adsorventes obtidos da biomassa de pinhão manso - Nacke, Herbert (2014)
This work aimed to evaluate the performance of three biosorbents obtained from the bark of fruit (biosorbent C), the endosperm (biosorbent E) and from the endosperm plus seed coat (biosorbent E + T) of Jatropha (Jatropha curcas L.) in the removal of metals chromium (Cr3+), cadmium (Cd2+), copper (Cu2+) and zinc (Zn2+) in aqueous solutions. To elucidate the properties of biosorbents, the characterization by infrared spectroscopy (IR), scanning electron microscopy (SEM) and determination of the point of zero charge (pHPCZ) of the materials was performed. The study of the optimal conditions and mechanisms that control the adsorption of the aforementioned metals by the biosorbents was performed through the influence of the solution pH, the mass of biosorbent, the contact time between the solution and the biosorbent, the initial concentration of metals in solution (adsorption isotherms) and the temperature during adsorptive process (thermodynamics). The adsorption kinetics was evaluated using the mathematical models of pseudofirst and pseudosecond order, Elovich and intraparticle diffusion. The adsorption isotherms were linearized by mathematical models of Langmuir, Freundlich and Dubinin-Radushkevich. Was also performed the comparision of the biosorbents with activated charcoal, since this material is the mainly adsorbent used in the sorption process of metallic contaminants. In the characterization of biosorbents was observed that all three materials have a structure with proteins, lignin, cellulose, hemicellulose, lignocellulose, hydroxyl, carboxylic, carbonyl and phenol groups, which enable bonds with metallic ions in solution. Furthermore, it was observed that the surface morphology of the biosorbents has irregular appearance, indicating a porous surface and good adsorptive capacity. The biosorbents show a pHPCZ between 5 and 6. The optimal conditions for the adsorptive process were: pH of 5.5 for the metals Cr3+ and Cd2+ and 5.0 to Cu2+ and Zn2+, 8.0 g L-1 of biosorbent mass per volume of solution and a contact time between the biosorbents and the contaminated solutions of 60 min for all metals. The results obtained in the adsorption kinetics indicate that for all metals in the study, the biosorbents showed a better fit by pseudosegunda order model, indicating the occurrence of chemical adsorption. Considering the maximum adsorption capacities obtained by the mathematical model of Langmuir, the biosorbent C presents the following order of removal: Cd2+ > Cr3+ > Zn2+ > Cu2+ (29.66; 22.11; 14.85 and 11.54 mg g-1); whereas for the biosorbent E the order was: Cu2+ > Cd2+ > Cr3+ > Zn2+ (20.47; 19.56; 18.20 and 15.88 mg g-1) and for the biosorbent E+T it was obtained: Cd2+ > Cu2+ > Cr3+ > Zn2+ (34.67; 22.91; 22.88 and 16,67 mg g-1). Regarding the adsorption form, the results showed that for all metals the chemisorption controls the adsorptive process, with the occurrence of mono-and multilayers for Cr3+ and monolayers for Cd2+, Cu2+ and Zn2+. Based on the results obtained in this work, it is possible affirm that the three biosorbents derived from the biomass of Jatropha have potential for the remediation of water resources contaminated with the metals Cr3+, Cd2+, Cu2+ and Zn2+, also providing an alternative use of the waste generated in biodiesel production of this species, increasing the sustainability of their supply chain